2014
DOI: 10.1310/hpj4904-369
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Effective Succession Planning in Health-System Pharmacy Departments

Abstract: Leadership succession planning is crucial to the continuity of the comprehensive vision of the hospital pharmacy department. Leadership development is arguably the main component of training and preparing pharmacists to assume managerial positions. Succession planning begins with a review of the organizational chart in the context of the institution's strategic plan. Then career ladders are developed and key positions that require succession plans are identified. Employee profiles and talent inventory should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…In healthcare, succession-planning practices are often limited, and the HAI/IPAC team identified the need for strategic planning to delineate desired leadership competencies and identify future high-potential leaders. Proactive succession planning involves identifying high potential individuals and formally developing them to assume leadership roles 4 , 5 . Traditionally ICPs have provided IPAC advice within the healthcare environment.…”
Section: Building Capacity For the Future Leaders Of Ipacmentioning
confidence: 99%
“…In healthcare, succession-planning practices are often limited, and the HAI/IPAC team identified the need for strategic planning to delineate desired leadership competencies and identify future high-potential leaders. Proactive succession planning involves identifying high potential individuals and formally developing them to assume leadership roles 4 , 5 . Traditionally ICPs have provided IPAC advice within the healthcare environment.…”
Section: Building Capacity For the Future Leaders Of Ipacmentioning
confidence: 99%
“…Among all of the extrinsic factors that have been studied, management support is the most discussed in 17 studies, for instance, Mehrtak et al (2014) in health-system pharmacy departments. They suggested that internal commitment programs to be included actively in promoting from within, a robust residency program, transparency in succession planning and support for advance degrees.…”
Section: Extrinsic Factors Associated With Succession Planning and Ma...mentioning
confidence: 99%
“…In fact, a 2016 national survey of local health departments in America revealed that only 39.5% of these departments had a formal succession plan (Darnell, Campbell, 2016). It was strongly recommended that healthcare institutions be proactive in developing formal SP strategies so as to reduce employee turnover in the health sector, particularly when recruiting numbers have been declining over the years (Trepanier, Crenshaw, 2013;Ellinger et al, 2014;Acree-Hamann, 2016;Donner et al, 2017;Phillips et al, 2018;Sierra, Calabrese, 2019).…”
Section: Theme 1: Assessing the Level Of Sp In Different Contextsmentioning
confidence: 99%